Differential expression of mechanotransduction complex genes in auditory/vestibular hair cells in zebrafish - Smith, Eliot T.; Sun, Peng; Yu, Shengyang Kevin; Raible, David W.; Nicolson, Teresa (Frontiers in Molecular Neuroscience, 2023)
Ciliated sensory cells such as photo- and olfactory receptors employ multiple types of opsins or hundreds of unique olfactory G-protein coupled receptors to respond to various wavelengths of light or odorants. With respect to hearing and balance, the mechanotransduction machinery involves fewer variants; however, emerging evidence suggests that specialization occurs at the molecular level. To address how the mechanotransduction complex varies in the inner ear, we characterized the expression of paralogous genes that encode components required for mechanotransduction in zebrafish hair cells using RNA-FISH and bioinformatic analysis. Our data indicate striking zonal differences in the expression of two components of the mechanotransduction complex which are known to physically interact, the transmembrane channel-like 1 and 2 (tmc1/2) family members and the calcium and integrin binding 2 and 3 (cib2/3) paralogues. tmc1, tmc2b, and cib3 are largely expressed in peripheral or extrastriolar hair cells, whereas tmc2a and cib2 are enriched in central or striolar hair cells. In addition, a gene implicated in deaf-blindness, ush1c, is highly enriched in a subset of extrastriolar hair cells. These results indicate that specific combinations of these components may optimize responses to mechanical stimuli in subtypes of sensory receptors within the inner ear.